Tribology in Sheet Rolling Technology - Azushima, Akira; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides an in-depth description of the fundamental tribological aspects of cold and hot sheet rollings. The author describes new developments in the rolling processes, the rolling oils, the rolling rolls and the structural materials resulting from sheet rolling technology and their practical applications. The author includes comprehensive details on both friction and lubrication in rolling.
Fundamental of Tribology -- Tribology in metalforming -- Fundamental of Rolling -- Tribology in Cold Sheet Rolling -- Tribology in hot sheet rolling.
Keywords: Building materials; Surfaces (Physics).; Mechanics, Applied; Solids; Structural Materials; Surface and Interface and Thin Film; Solid Mechanics